Improving Students’ Social Studies Learning Outcomes through the Role Playing Method in Fifth Grade of MI Islamiyah Sumberrejo - Amelia, Agusti; Irnalita, Irnalita (GeoEdu Insight Journal, 2026)
Purpose of the study: This study aims to improve Social Studies learning outcomes and student participation through the implementation of the Role Playing method in fifth-grade students of MI Islamiyah Sumberrejo, particularly on historical material about the Indonesian proclamation of independence. Methodology: This research used Classroom Action Research (CAR) model by Suharsimi Arikunto conducted in two cycles. Data were collected through tests, observation sheets, interviews, and documentation. Instruments included pre-test and post-test, observation sheets, and school records. Data were analyzed using descriptive quantitative and qualitative techniques supported by simple calculation software such as Microsoft Excel. Main Findings: The findings show a significant improvement in students’ learning outcomes after the implementation of the Role Playing method. Student mastery increased from 23% in the preliminary stage to 80% in Cycle II, with average scores rising from 61.6 to 73.6. Teacher activity improved from 61% to 82%, while student activity increased from 59% to 81%. The method also enhanced students’ participation, motivation, and understanding of historical learning materials. Novelty/Originality of this study: This study is novel because it applies the Role Playing method specifically to Indonesian proclamation history in a Madrasah Ibtidaiyah context using Classroom Action Research. It not only focuses on cognitive improvement but also emphasizes active student participation. This research contributes new insight into integrating dramatization-based learning in elementary Social Studies education to enhance engagement and outcomes.